2023
DOI: 10.33087/ekonomis.v7i1.1032
|View full text |Cite
|
Sign up to set email alerts
|

Kemiskinan dan Faktor-Faktor yang Mempengaruhinya di Indonesia

Abstract: Poverty alleviation in Indonesia is strongly influenced by other economic variables. The three main factors used to measure its effect on poverty are economic growth, unemployment and inflation. This study aims to examine and analyze the relationship between theoretical and empirical balance between economic growth, unemployment rate and inflation rate with poverty in Indonesia both in the short and long term. The estimation method used is a dynamic econometric model with the cointegration approach and the Err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The choice of ECM aimed to prevent spurious regression, which indicates that research variables do not relate to one another, even though the regression results produce sizable coefficients and a high coefficient of determination (Ekananda, 2014). Numerous prior investigations have demonstrated that this methodology is suitable for examining how independent and dependent variables are related to one another over both in the short and long terms (Payapo et al, 2023;Setiadi & Mafruhat, 2023;Wau, 2022). Therefore, to avoid spurious regression between variables in the model, ECM analysis was conducted based on the cointegration test to observe the influence in the short and long run.…”
Section: Methodsmentioning
confidence: 99%
“…The choice of ECM aimed to prevent spurious regression, which indicates that research variables do not relate to one another, even though the regression results produce sizable coefficients and a high coefficient of determination (Ekananda, 2014). Numerous prior investigations have demonstrated that this methodology is suitable for examining how independent and dependent variables are related to one another over both in the short and long terms (Payapo et al, 2023;Setiadi & Mafruhat, 2023;Wau, 2022). Therefore, to avoid spurious regression between variables in the model, ECM analysis was conducted based on the cointegration test to observe the influence in the short and long run.…”
Section: Methodsmentioning
confidence: 99%